A theoretical justification and framework for scenario planning in SMEs. Issue 4 (2nd October 2021) - Scott, Kyle
ABSTRACT: This article provides a theoretical framework and justification for scenario planning, a practice that enables small businesses to be more agile and resilient. Agile and resilient companies are better positioned to succeed in an unknown future. Scenario planning offers a way for companies to think creatively about opportunities, threats, and solutions while still operating successfully in the known present. Compared to strategic planning, scenario planning is less resource intensive and therefore offers small businesses a more realistic way to build for the future. This article contrasts scenario planning with strategic planning while providing recommendations for adapting the former into a small business environment.